LATE ARCHAEOLOGY IN THE LOWER MALA VALLEY, SANTA CRUZ DE FLORES DISTRICT, CAÑETE-LIMA - Mejía Aranguren, Luisa (2015)
This investigation was initiated at the request of the mayor of the district of Santa Cruz de Flores and the National University Federico Villarreal (specialty of Anthropology and Archaeology) in order to conduct an interdisciplinary study on the cultural heritage of the district. Painfully the project did not reach its final phase (publication), but archaeological field stage if culminate reached. In this way we meddle in social understanding and cultural archaeological sites jurisdiction, identifying local people apparently migrated or were displaced to the bottom from the village of Callaguaya (upper section of Mala), at the end of the period Middle Horizon (600-1000 AD.) or early Late Intermediate Period (1000-1470 AD.). Then they will be strategically occupied by the Incas during the Late Horizon (1470-1532 AD.) Period for control and management of the area, demonstrating this process through formal and material elements attributes discussed in this document.